CARBON STOCKS IN MINED AREA RECLAIMED BY LEGUMINOUS TREES AND SLUDGE - Balieiro,Fabiano de Carvalho (2017)
ABSTRACT Few studies have been carried out on aboveground (or belowground) and soil/substrate C accumulation in severely degraded areas, such as mined areas. The present study was developed in order to find a recovery strategy for a mined area and characterize its potential for C sequestration by planting two nitrogen-fixing Brazilian tree species (Mimosa caesalpiniifolia Benth and M. bimucronata (DC.) O. Kuntze). Sewage sludge was included in the experimental design. An experiment under randomized block condition and 2 x 5 factorial design with four replications were defined and carried out, in Rio de Janeiro State, Brazil. The treatments consisted of a combination of both tree species and five sewage sludge doses (0, 2.85; 5.70; 11.40 and 22.80 Mg ha-1). M. caesalpiniifolia grows better (p<0.05) in reclaimed areas than M. bimucronata, even though neither the height nor the basal area of both species responded to the sludge application. Carbon stock in the tree trunks differ between species (27.3 and 14.3 Mg ha-1, for M. caesalpinifolia and M. bimucronata, respectively), and was influenced by the doses of sewage sludge, whereas the soil carbon stock (0-10 cm) did not differ between species and doses (12.0 and 12.2 Mg ha-1, for M. caesalpiniifolia and M. bimucronata, respectively). Soil fertility in the degraded site was found to be improved by legume trees six years after planting, with a small influence of the sewage sludge level. Mined areas recovered with legume trees can sequestrate significant amounts of C both in aboveground biomass and soil in a short period of time.